PEMBELAAN MUHAMMAD MUSTHOFA AZAMI DALAM PENULISAN HADIS QABLA TADWIN - Moh. Misbakhul Khoir , (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
The conversation around the writing of Hadith is always an interesting thing. This is due to the view that the Hadith was written late a century after the Prophet's death. Ulama argue that after the death of the Prophet until the end of the 1st century Hijriyah, Hadith was only narrated orally from rote-memorization. This condition is certainly very unfavorable for the Hadith, because without a disciplined writing like the Qur'an, the authenticity of the Hadith is highly questionable. In this modern century, a scholar named M. Musthofa Azumi emerged. He conducted in-depth research on the history of writing hadith. The results of his research, have changed the viewpoint of the temporary scholars who stated that Hadith was not written for a century, Azumi concluded that the writing of Hadith had actually been started since the time of the Prophet, and continued to develop until its golden peak, namely the 2nd century Hijrival. This is because there is a lot of strong evidence about it. Azami's evidence is used as an argument to criticize the views of the ulama and refute the negative accusations made by Western orientalists against the Prophet's Hadith.